Islamic Education for Women in Madrasah Mu’allimat - Syahdara Anisa Makruf; Sutrisno Sutrisno; Zalik Nuryana (Jurnal Pendidikan Islam, 2022)
Madrasah Mu'allimat was established as the first women's school to develop graduates with prophetic leadership. This study aims to examine the institution and its educational practices to develop and nurture prophetic leadership for the students. This type of research is descriptive-qualitative. Data were obtained using in-depth interview techniques, participant observation, and documentation. The analysis of data is conducted through reduction, presentation, verification, and conclusion. The results of the study show that Madrasah Mu'allimat takes into consideration five competencies for its educational service: science, personality, skills, humanity, and social movements. These five competencies are designed towards developing women's leadership competencies based on the prophetic spirit of Islam. A systematic and continuous development program for student is one of the contributing factors to the success of Madrasah Mu'allimat. The institution strives to deliver its educational service and maintain its position as the leading and oldest women's madrasah in Indonesia.